Increased Energy Expenditure, Lipolysis and Hyperinsulinemia Confer Resistance to Central Obesity and Type 2 Diabetes in Mice Lacking Alpha2α-Adrenoceptors - Ruohonen S; Valve L; Tuomainen K; Ailanen L; Röyttä M; Manz G; Baur N; Joos T; Savontaus E; Scheinin M (My University, 2022)
The α2A-adrenoceptors (ARs) are Gi-coupled receptors, which prejunctionally inhibit the release of norepinephrine (NE) and epinephrine (Epi), and postjunctionally insulin secretion and lipolysis. We have earlier shown that α2A-/- mice display sympathetic hyperactivity, hyperinsulinemia and improved glucose tolerance. Here we employed α2A-/- mice and placed the mice on a high-fat diet (HFD) to test the hypothesis that lack of α2A-ARs protects from diet-induced obesity (DIO) and type 2 diabetes (T2D). In addition, high caloric diet was combined with running wheel exercise to test the interaction of diet and exercise. HFD was obesogenic in both genotypes, but α2A-/- mice accumulated less visceral fat than their WT controls, were protected from T2D, and their insulin secretion was unaltered by the diet. Lack of α2A-ARs associated with increased sympatho-adrenal tone, which resulted in increased energy expenditure and fat oxidation rate potentiated by HFD. Fittingly, α2A-/- mice displayed enhanced lipolytic responses to Epi, and increased fecal lipids suggesting altered fat mobilization and absorption. Subcutaneous white fat appeared to be thermogenically more active (measured as Ucp1 mRNA expression) in α2A-/- mice, and brown fat showed an increased response to norepinephrine. Exercise was effective in reducing total body adiposity and increasing lean mass in both genotypes, but there was a significant diet-genotype interaction, as even modestly increased physical activity combined with lack of α2A-AR signalling promoted weight loss more efficiently than exercise with normal α2A-AR function. These results suggest that blockade of α2A-ARs may be exploited to reduce visceral fat and to improve insulin secretion.
.